Study of the Possibility of Honey Wine Production Using New Active Dry Yeasts and Yeasts Derivatives - Bakhshetsyan, Shahane; Gevorgyan, Elyanora; Mikayelyan, Mikayel (ՀԱԱՀ հիմնադրամ)
Honey wine, also known as a fermented beverage made from natural honey, is believed to be one of the earliest alcoholic drinks created by ancient humans thousands of years ago, long before the discovery of grape wine. Our research aims to produce wine from honey collected in the Armenian mountains. A series of articles dedicated to the study of the possibility of obtaining alcoholic beverages made by fermenting natural honey (honey wine) using different types of dry active yeast and yeast autolysis derivatives. The data obtained from the research results will be interesting from both the scientific and production points of view. This will allow us to conclude that the selected yeasts can be used for producing such alcoholic beverages.
Keywords: Food Science and Technology